Marketing Assistance for Processed Agricultural Products in Kandangtepus Village, Senduro District, Lumajang Regency - Noverma Noverma (Jurnal Abdi Masyarakat (JAM), 2023)
The village of Kendang Tepus Lumajang is an area rich in agricultural products and currently has several processed products such as banana chips, coffee and milk. The problem experienced is that business actors have difficulty in marketing them, thus making it difficult for this business to develop. Overcoming these problems, then the aim of this research is to provide assistance in product marketing techniques. Assistance is carried out using the Community Based Research (CBR) approach. The stages begin with training on packaging making, efforts to obtain official permits so that products are more reliable and then carry out extensive promotions. The results of the current attenuation are that most people already know marketing techniques ranging from packaging methods to make it more attractive, official permits to be marketed more broadly and promotional techniques both by opening a place of business, collaboration with souvenirs and also marketing through social media.